INNOVATIVE TECHNOLOGICAL AND PEDAGOGICAL APPROACHES TO THE TRANSITION OF CLASSES TO STUDENTS - X. Ch. Dusyarov; S. X. Dusyarov (Journals Park Publishing, 2024)
This article describes educational materials related to the organization of the educational process based on innovative technological and pedagogical approaches to the organization of classes.
Keywords: Education, training, training, innovation, technology, pedagogy, approach.